2018
DOI: 10.1177/0020764018808548
|View full text |Cite
|
Sign up to set email alerts
|

Geopolitical factors and mental health I

Abstract: Natural and man-made disasters carry with them major burden and very often the focus is on immediate survival and management of resulting infectious diseases. The impact of disasters directly and indirectly on the well-being and mental health of those affected often gets ignored. The reasons are often stigma and lack of attention to mental health consequences. In addition, often the focus is on preventing the spread of infectious diseases such as waterborne or airborne diseases. This is further complicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Previous research describes the scarcity of humanitarian assistance for mental health (Persaud et al, 2018a) and an index has been proposed to facilitate its allocation based on compassion, assertive action, pragmatism, and evidence (Persaud et al, 2018b). A policy report identifies four main reasons for underinvestment in mental disorders in LMICs: lack of understanding of mental disorders, difficulties in measuring return on investment, stigma, and competing priorities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research describes the scarcity of humanitarian assistance for mental health (Persaud et al, 2018a) and an index has been proposed to facilitate its allocation based on compassion, assertive action, pragmatism, and evidence (Persaud et al, 2018b). A policy report identifies four main reasons for underinvestment in mental disorders in LMICs: lack of understanding of mental disorders, difficulties in measuring return on investment, stigma, and competing priorities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the new community's response will affect their wellbeing. 39 Given the new situation faced both by refugees and the new society of the host countries, integration strategy is considered as the best approach for refugees' acculturation within the community.…”
Section: Government Input For Refugees Empowermentmentioning
confidence: 99%
“…This facial trauma causes physical as well as psychological impact on individuals. According to WHO around 450 million people suffer from mental disorders and about 11% of sufferers are due to all diseases and injuries in the world 2 . Studies have shown that patients with facial trauma are more prone to depression and anxiety disorders within 1 year of trauma due to facial disfigurement 3 .…”
Section: Introductionmentioning
confidence: 99%